El derecho de veto en el Consejo de Seguridad de Naciones Unidas: la historia de la válvula de seguridad que paralizó el sistema (2008)
This article presents an analysis the veto right in the Security Council of the United Nations from its creation until the present time. It begins with the origins of the veto, as well as the determinative reasons for its establishment. It looks at how the veto has been used and, as alleged by some, “abused” by some permanent members of the Security Council. Taking into account that the majority of doctrinal works referring to this issue were written some decades ago, it is timely to analyze how this right has developed from the era of the creation of the United Nations until the present.